Deforming the Reform The Impact of Elites on Romania's Post-accession Europeanization - Martin-Russu, Luana (Contributions to Political Science, 2022)
This open access book presents an actor-centered study on Europeanization, based on the assumption that EU-driven reforms are highly dependent on the behavior and interests of the key domestic actors. Whether or not a state pursues a European and democratic agenda depends on domestic lawmakers. Further, political elites are pre-eminent in deciding on the nature, form and content of any law, and on the extent to which the rule of law is actually enforced. Elites can overcome structural or institutional barriers that stand in the way of achieving their goals. The empirical study on Romania presented here lends this observation a more profound meaning: it shows how, in contexts where high level corruption is the norm rather than the exception, self-serving political elites cannot be expected to genuinely commit to adopting sound anti-corruption reform. The book is an inquiry into the motivations that drive legislators to make particular decisions, but also into the structural characteristics and dynamics of the elite that invite a selfish rather than responsible and responsive behaviour. This publication was supported by funds from the Publication Fund for Open Access Monographs of the Federal State of Brandenburg, Germany.